Derechos humanos, educación y género: reflexiones universitarias desde la metodología del aprendizaje basado en investigación (Experiencias) - Salgado Guifarro, Onix Alejandra (2024)
Higher education in Honduras faces multiple challenges due to the social context that affects its environment and therefore its students, which requires that these institutions assume a leading role in identifying and addressing territorial realities through teaching-learning practices that promote research and participation of university students in the construction of knowledge for their awareness and action to improve their environment. The objective of this research is to reflect the analysis of the International Relations students of the Central American Technological University on the perspective of human rights, education and gender contemplated in the government plan of Honduras 2022- 2026 using Research Based Learning (RBL) methodology tools, a study developed in the subject “Management of Cooperation and Humanitarian Aid” where 16 students participated in documentary reviews, tree diagrams, focus groups, SWOT analysis and the elaboration of an opinion article as a final project. This educational experience underscored the importance of cooperating and creating spaces for research linked to the Honduran reality in order to promote academic freedom within the classroom with active dynamics, including the evaluation of thematic content and the understanding of current regulations and their real impact on society. In addition, the proposal encourages self-taught practice, allowing students to assume responsibility and autonomy in their learning, with the teacher’s role being crucial in guiding and supporting the development of these skills.